The Development of the Insurance Market in the Context of Digitalization and Consolidation - M. A. Loskutova (Учёт. Анализ. Аудит, 2020)
The relevance of the study is associated with the accelerated pace of automation and digitalization, which open up new opportunities for increasing the efficiency of insurance market participants. This process will help to ensure cost savings and increased revenues. The aim of the work is to determine the current trends in the penetration of digital technologies into the insurance market. The subject of the research is the processes of digitalization and consolidation of the insurance market. The research used the methods of horizontal and vertical statistical analysis. The absolute and relative deviations were calculated to determine the dynamics of the main phenomena and processes. The analysis of the peculiarities of the development of the insurance market in the context of digitalization is carried out and the prospects for further development are indicated. Over the past year, there has been a decrease in the intensity of the development of Internet communication between companies and clients in the insurance market; on the other hand, there has been a positive increase in expenses for advertising and other means of communication with the target audience. New insurance products are emerging due to the ability to collect more data on customers of insurance companies. The results obtained can be used to substantiate the development paths of individual insurance companies, and the research can be interesting for practice.